Аналіз впливу основних видів дефектів та пошкоджень на несучу здатність залізобетонних елементів - Лободанов, М. М.; Вегера, П. І.; Бліхарський, З. Я.; Lobodanov, M.; Vegera, P.; Blikharskyy, Z. (Видавництво Львівської політехніки, 2018)
За сучасними економічними тенденціями необхідно змінювати призначення будівель та споруд. Це зазвичай призводить до зміни величини та характеру впливу корисного навантаження на будівельні конструкції, з необхідністю оцінювання технічного стану та заміною або підсиленням елементів. Важливе місце в обстеженні, реконструкції будівель і споруд належить визначенню залишкової несучої здатності елементів. Особливо це стосується залізобетонних елементів, які поширені в України. Важливим аспектом визначення залишкової несучої здатності згинаних залізобетонних елементів є дослідження впливу дефектів і пошкоджень на зміну міцності та деформативності елемента. Оскільки залізобетон є складним композитним матеріалом, визначення впливу і прогнозування дії на нього різних видів дефектів і пошкоджень є складним завданням. Переважно це стосується комбінації різних дефектів і пошкоджень, яка підвищує варіативність дії різних внутрішніх і зовнішніх факторів під час розрахунку і формування методології визначення їх впливу. Досліджено вплив дефектів і пошкоджень на залишкову несучу здатність пошкоджених залізобетонних елементів з акцентуацією на згинані залізобетонні елементи. Розглянуто дію різних видів дефектів і пошкоджень та їхніх певних комбінацій, які призводять до зміни характеристик міцності та деформативності елемента, і можливої зміни роботи елемента.

In nowadays economic trends, there is a need in changes in the usage of buildings and structures. This usually leads to the changes loading and character of the loadings type on the building structures, with the subsequent need to assess the technical condition and the replacement or enhancement of certain elements. Also, objects, which need the reconstruction in order to be reequipped or changed it functionality, that have designs which were used under the influence of an aggressive environment or other factors which were not taken into account. This increases the difficulty of the rating of the technical condition of individual constructions and further reconstruction. An important place in the possibility of reconstruction of buildings and structures is determining to the residual bearing capacity of the elements. This is especially true for reinforced concrete elements widely used on the territory of Ukraine. An important aspect of determining the residual ability of bending reinforced concrete elements is the study of the effect of defects and damage on the changes in strength and deformation ability of the element. As reinforced concrete is a complex composite material, the determining of impact and predicting the effects on it of various types of defects and damage is a rather difficult task. This mainly concerns the combination of various defects and damage, which increases the variability of the various internal and external factors in the calculation and further formation of the methodology of determining the impact. Therefore, this issue is not completely solved and requires further researching. In the article, the researches of influence of defects and damages on residual bearing ability of damaged reinforced concrete elements with accentuation on bending reinforced concrete beams are analyzed. The main types of defects of reinforced concrete beams are the corrosion of the reinforcement, the reduced crosssectional area, defects obtained in the manufacture, transportation and operation of structures With consideration of the action of various types of defects and damage and their certain combinations, which lead to changes in the characteristics of the strength and deformability of the element, and the possible change in the operation of the element.
Analysis of influence of main types of defects and damage on the bearing capasity of reinforced concrete elements
Keywords: згинані залізобетонні елементи; залізобетонна балка; пошкодження; дефекти; несуча здатність; bending elements; reinforced concrete beam; damages; defects; bearing capacity; 624.046.2; 539.3